Strategi Pemasaran dalam Meningkatkan Jumlah Mahasiswa pada Program Studi Manajemen Keuangan Syariah (Studi Komparatif Uin Syekh Ali Hasan Ahmad Addary Padangsidimpuan dan Uin Sunan Kalijaga) - Azwar Hamid; M. Fauzan (Universitas Muhammadiyah Surabaya, 2023)
The title of this research is Marketing Strategy in Increasing the Number of Students in Sharia Financial Management Study Programme (Comparative Study of UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan and UIN Sunan Kalijaga). The general objectives of this study are to analyse the efforts that have been made in increasing the number of students at the Sharia Financial Management Study Program of UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan and UIN Sunan Kalijaga, to provide solutions to the problems faced related to marketing strategies at the Sharia Financial Management Study Program of UIN Sheikh Ali Hasan Ahmad Addary Padangsidimpuan and UIN Sunan Kalijaga, and to analyse the level of success in planning, implementing, and implementing promotional strategies at the Sharia Financial Management Study Program of UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan and UIN Sunan Kalijaga. This research approach uses a qualitative descriptive method. The subjects of this research are the Dean, Head of Study Programme, Alumni, and Students of the Faculty of Economics and Islamic Business of UIN Sheikh Ali Hasan Ahmad Addary and UIN Sunan Kalijaga. This research data analysis technique uses SWOT analysis (Strengths, Weakness, Opportunities, and Threats). The results of this study are expected to provide input and suggestions to the Sharia Financial Management Study Program, Faculty of Economics and Islamic Business, UIN Sheikh Ali Ahmad Addary Padangsidimpuan related to marketing strategies that have been carried out in the Sharia Financial Management Study Program, Faculty of Economics and Islamic Business, UIN Sunan Kalijaga to be implemented and practiced in the Sharia Financial Management Study Program, Faculty of Economics and Islamic Business, UIN Syekh Ali Ahmad Addary Padangsidimpuan so that there is an increase in the number of students in accordance with the ratio of existing lecturers. Then it will have an impact on increasing the accreditation of the Sharia Financial Management Study Programme, Faculty of Economics and Islamic Business, UIN Sheikh Ali Ahmad Addary Padangsidimpuan.